EGFR EQUATIONS: EVALUATION AGAINST REFERENCE GFR IN INDIAN POPULATION - T. PAVANI KIRANMAI; SIRAJ AHMED KHAN; K.S.S SAI BABA; KAVITA NALLAPAREDDY; PRISCILLA CHANDRAN. (International Journal of Pharma and Bio Sciences, 2015)
Glomerular filtration rate (GFR) is the best overall index to measure and monitor kidney function. Older method to measure GFR by using Inulin was cumbersome and cannot be used in clinical practice. Serum creatinine based equations are the choice of GFR estimation in present clinical setting. In this study, we have compared the creatinine based equations with DTPA scan GFR (Reference GFR) measurements and found that serum creatinine based equations either underestimated or overestimated GFR. We found that Cockcroft –Gault equation was found to have least negative bias with reference GFR after adjustment for body surface area, followed by MDRD (6-Variable) equation.